Oxygen delivery from hyperbarically loaded microtanks extends cell viability in anoxic environments. (June 2015) - Cook, Colin A.; Hahn, Kathryn C.; Morrissette-McAlmon, Justin B.F.; Grayson, Warren L.
Abstract: Oxygen diffusion limitations within nascent tissue engineered (TE) grafts lead to the development of hypoxic regions, cell death, and graft failure. Previous efforts have been made to deliver oxygen within TE scaffolds, including peroxide-doping, perfluorocarbons, and hyperbaric oxygen therapy, to mitigate these effects and help maintain post transplantation cell viability, but these have suffered from significant drawbacks. Here we present a novel approach utilizing polymeric hollow-core microspheres that can be hyperbarically loaded with oxygen and subsequently provide prolonged oxygen delivery. These oxygen carriers are termed, microtanks . With an interest in orthopedic applications, we combined microtanks within polycaprolactone to form solid phase constructs with oxygen delivery capabilities. The mathematical laws governing oxygen delivery from microtank-loaded constructs are developed along with empirical validation. Constructs achieved periods of oxygen delivery out to 6 days, which was shown to prolong the survival of human adipose derived stem cells (hASCs) and human umbilical vein endothelial cells (HUVECs) as well as to enhance their cellular morphology under anoxic conditions. The results of this study suggest the microtank approach may be a feasible means of maintaining cell viability in TE scaffolds during the critical period of vascularization in vivo .